Mild Traumatic Brain Injury Induces Mitochondrial Calcium Overload and Triggers the Upregulation of NCLX in the Hippocampus - Rodrigo G. Mira; Rodrigo A. Quintanilla; Waldo Cerpa (MDPI AG, 2023)
Traumatic brain injury (TBI) is brain damage due to external forces. Mild TBI (mTBI) is the most common form of TBI, and repeated mTBI is a risk factor for developing neurodegenerative diseases. Several mechanisms of neuronal damage have been described in the cortex and hippocampus, including mitochondrial dysfunction. However, up until now, there have been no studies evaluating mitochondrial calcium dynamics. Here, we evaluated mitochondrial calcium dynamics in an mTBI model in mice using isolated hippocampal mitochondria for biochemical studies. We observed that 24 h after mTBI, there is a decrease in mitochondrial membrane potential and an increase in basal matrix calcium levels. These findings are accompanied by increased mitochondrial calcium efflux and no changes in mitochondrial calcium uptake. We also observed an increase in NCLX protein levels and calcium retention capacity. Our results suggest that under mTBI, the hippocampal cells respond by incrementing NCLX levels to restore mitochondrial function.